2018
DOI: 10.1177/2050640618767594
|View full text |Cite
|
Sign up to set email alerts
|

Propofol for gastrointestinal endoscopy

Abstract: Most gastrointestinal endoscopic procedures are now performed with sedation. Moderate sedation using benzodiazepines and opioids continues to be widely used, but propofol sedation is becoming more popular because its unique pharmacokinetic properties make endoscopy almost painless, with a very predictable and rapid recovery process. There is controversy as to whether propofol should be administered only by anesthesia professionals. According to published values, endoscopist-directed propofol has a lower mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 31 publications
0
44
0
3
Order By: Relevance
“…Propofol alone as a sedative in colonoscopy may require a larger dose to maintain a sufficient depth of anesthesia and supplement with low-dose opioids could reduce the stimulation on autonomic nerves system caused by colonoscopy [15], and make the patient recovery faster. Opioids sedatives have been widely used in enteroscopy [16]. Fahima et al [17] found that combined administration of opioids with propofol in colonoscopy was statistically safe to the patients with higher satisfaction feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol alone as a sedative in colonoscopy may require a larger dose to maintain a sufficient depth of anesthesia and supplement with low-dose opioids could reduce the stimulation on autonomic nerves system caused by colonoscopy [15], and make the patient recovery faster. Opioids sedatives have been widely used in enteroscopy [16]. Fahima et al [17] found that combined administration of opioids with propofol in colonoscopy was statistically safe to the patients with higher satisfaction feedback.…”
Section: Introductionmentioning
confidence: 99%
“…This particular benefit of propofol sedation is likely to offset some of the costs resulting from decreased throughput and longer waitlists that are likely with conscious sedation [ 17 ]. The differences in the pharmacokinetics of propofol in comparison with midazolam–fentanyl include a faster onset of action, occurring in seconds rather than minutes [ 18 , 19 ]. As a result, the time from injection of sedative and intubation is likely to be shorter with significant cost and time savings.…”
Section: Challenges To Macmentioning
confidence: 99%
“…The U.S. Food and Drug Administration recently denied a petition by gastroenterologists seeking the removal of this particular restriction [ 8 ]. However, these warnings do not take into account recent evidence on the safety of NAAP in a variety of routine and advanced endoscopic procedures, including endoscopic ultrasound (EUS) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%